Close approximations to the sound of a cochlear implant - Dorman, Michael F.; Natale, Sarah C.; Stohl, Joshua S.; Felder, Jenna (Frontiers in Human Neuroscience, 2024)
Cochlear implant (CI) systems differ in terms of electrode design and signal processing. It is likely that patients fit with different implant systems will experience different percepts when presented speech via their implant. The sound quality of speech can be evaluated by asking single-sided-deaf (SSD) listeners fit with a cochlear implant (CI) to modify clean signals presented to their typically hearing ear to match the sound quality of signals presented to their CI ear. In this paper, we describe very close matches to CI sound quality, i.e., similarity ratings of 9.5 to 10 on a 10-point scale, by ten patients fit with a 28 mm electrode array and MED EL signal processing. The modifications required to make close approximations to CI sound quality fell into two groups: One consisted of a restricted frequency bandwidth and spectral smearing while a second was characterized by a wide bandwidth and no spectral smearing. Both sets of modifications were different from those found for patients with shorter electrode arrays who chose upshifts in voice pitch and formant frequencies to match CI sound quality. The data from matching-based metrics of CI sound quality document that speech sound-quality differs for patients fit with different CIs and among patients fit with the same CI. no change -10 no change 5 no no none no 10 50% -10 no change 5 no no BP 0.4-1.0 kHz no 10 40% no change no change 5 no yes LPF 1.0 kHz no 9.9 10% no change no change none no no LP 3.0 kHz Sine VC -6 dB 9.5 no change 5 no change none no no LP 0.7 kHz no 9.5 50% 20 no change none yes no LP 3.0 kHz no 9.5 no change -15 no change 3 no yes BP 0.4-4.2 kHz no 9.5 no change no change 100 1 no no HPF 0.3 kHz no 9.5 no change -29 -25 9 no no LPF 1.7 kHz no 9.5 10 90% no change no change 4.5 no yes LPF 1.2 kHz no 9.5